2015
DOI: 10.1007/s12274-015-0776-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel hydrogen storage properties of palladium nanocrystals activated by a pentagonal cyclic twinned structure

Abstract: Researchers appear to have neglected a special form of crystallites, pentagonal cyclic twinning, in which an obvious two-dimensional lattice expansion exists leading to novel physical-chemical properties associated with the changes in geometric and electronic structures. Using the storage and release of hydrogen in Pd nanocrystals as a probe, we have found that icosahedral pentagonal cyclic twinned Pd nanocrystals had distinct hydrogen storage properties, due to the two-dimensional lattice expansions, quite di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Notably, hydrogen, as the smallest atom, is easily incorporated with metals to form metal hydrides. Metal hydride complexes are key intermediates in proton reduction, H 2 oxidation, and CO 2 hydrogenation. However, implementing a metal hydride system as an alkaline HER catalyst remains a challenge, even though the reaction is performed in a H 2 -enriched environment. The major limiting reasons are that traditional metal hydrides obtained under high-pressure conditions are unstable and hydrogen atoms gradually leach out over time even at room temperature; furthermore, the low adsorption of intermediates on usual monometal-component hydrides is not favorable for the alkaline HER. , …”
mentioning
confidence: 99%
“…Notably, hydrogen, as the smallest atom, is easily incorporated with metals to form metal hydrides. Metal hydride complexes are key intermediates in proton reduction, H 2 oxidation, and CO 2 hydrogenation. However, implementing a metal hydride system as an alkaline HER catalyst remains a challenge, even though the reaction is performed in a H 2 -enriched environment. The major limiting reasons are that traditional metal hydrides obtained under high-pressure conditions are unstable and hydrogen atoms gradually leach out over time even at room temperature; furthermore, the low adsorption of intermediates on usual monometal-component hydrides is not favorable for the alkaline HER. , …”
mentioning
confidence: 99%
“…The intrinsic PCT consists of 20 (111) faceted tetrahedral units with 30 twin boundaries, in which a two-dimensional (2D) lattice expansion exists. The novel properties of metal NCs are induced by expansion due to the changes in geometry and electronic structure . For the hydrogenation reaction, the thermodynamics of the reaction is regarded as a key point for understanding the nanostructural effects on the properties of the metal hydrides.…”
mentioning
confidence: 99%
“…Recently, Xie et al found that icosahedral PdH 0.706 NCs and octahedral PdH 0.706 NCs could be produced by charging icosahedral Pd NCs and octahedral Pd NCs ( pre-treated with I − ) in H 2 at 2 atm pressure for 1 h at room temperature. 44 Powder X-ray diffraction (PXRD) patterns indicated that the diffraction peaks of both the obtained PdH 0.706 shifted to Fig. 2 Representative nonmetallic elements in the periodic table of the elements used for insertion into the Pd lattice to form binary PdL x .…”
Section: Hydrogen Atom-doped Pd Nanomaterialsmentioning
confidence: 99%